2010
DOI: 10.1007/s00535-010-0223-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in children: epidemiological analysis of the nationwide IBD registry in Japan

Abstract: The nationwide registry in Japan showed IBD in children has clinical features that are distinct from those in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 35 publications
10
98
3
3
Order By: Relevance
“…Congruent with previous Asian studies, including data from China (14,16,24,46) , Japan (2,15,27,43) , Korea (42,44) , Singapore (21) , India (9) and Sri Lanka (35) , our observation have demonstrated a male predominance in CD, which is discordant with majority of the western studies. Such discrepancy may be sex-related differences in triggering or predisposing factors of CD between Asian and Western populations.…”
Section: Discussioncontrasting
confidence: 35%
“…Congruent with previous Asian studies, including data from China (14,16,24,46) , Japan (2,15,27,43) , Korea (42,44) , Singapore (21) , India (9) and Sri Lanka (35) , our observation have demonstrated a male predominance in CD, which is discordant with majority of the western studies. Such discrepancy may be sex-related differences in triggering or predisposing factors of CD between Asian and Western populations.…”
Section: Discussioncontrasting
confidence: 35%
“…Najčešći fenotip Crohnove bolesti prema Montrealskoj klasifi kaciji je ileokolični oblik bolesti (L3), a ulceroznog kolitisa ekstenzivni kolitis (E3) (2,12,13,(21)(22)(23)(24)(25), odnosno prema Pariškoj klasifi kaciji pankolitis (E4), kojim se zahvaćeno područje širi i proksimalno od hepatične fl eksure (3,17). U mlađe djece oboljele od Crohnove bolesti češće je zahvaćeno debelo crijevo, a u adolescenata terminalni ileum (2,25), dok je u ulceroznom kolitisu nađeno značajno manje proktitisa u mlađe djece nego u adolescenata (24,25). Perianalna bolest u djece oboljele od Crohnove bolesti nalazi se u njih 10 % pri postavljanju dijagnoze (26).…”
Section: Osobitosti Kroničnih Upalnih Bolesti Crijeva U Djeceunclassified
“…Registri i u ovom području imaju bitnu ulogu, jer su baš oni pridonijeli izradi Montrealske i Pariške klasifi kacije. Iz njih smo saznali koji je najčešći fenotip bolesti pri postavljanju dijagnoze (2,3,12,13,17,(21)(22)(23)(24)(25), zatim da je fenotip u djece dobno ovisan (2, 24,25), a poslužili su i za opis novih, atipičnih oblika bolesti (3). Na temelju podataka o manjoj učestalosti proktitisa u mlađe djece postavljen je temelj za kasniji opis fenomena "pošte-de rektuma" (engl.…”
Section: Fenotip Bolestiunclassified
“…Not all the studies applied statistical analysis to changing rates over time: overall one-fifth of the studies showed increasing UC in children. A recent report has characterised patterns of U C i n J a p a n e s e c h i l d r e n w i t h d i r e c t comparison to adults in that country (Ishige et al 2010). A long-standing register was examined for the patterns of disease in children and adults.…”
Section: Epidemiology Of Uc In Children and Adolescentsmentioning
confidence: 99%